2011
DOI: 10.1111/j.1570-7458.2011.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular hydrocarbons as contact sex pheromone in the parasitoid Dibrachys cavus

Abstract: Cuticular hydrocarbons (CHCs) cover the cuticle of virtually any insect and do not only protect them from desiccation, but also possess various communicative functions. Previous studies suggested a function as contact sex pheromones in the parasitic wasp family Pteromalidae, but further species need to be studied before more general conclusions are possible. Here, we demonstrate a contact sex pheromone in females of Dibrachys cavus (Walker) (Hymenoptera: Pteromalidae). Males of this parasitoid were arrested on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 41 publications
1
55
0
Order By: Relevance
“…The non-polar CHCs have been extensively investigated over the past three decades with respect to their role as semiochemicals (Howard, 1993;Singer, 1998;Howard and Blomquist, 2005). A multitude of studies have shown that CHCs are not only involved in the diverse interactions of social insects (Greene and Gordon, 2003;Endler et al, 2004;van Zweden and d'Ettorre, 2010) but also used by many solitary insects as contact stimuli when searching for oviposition sites (Colazza et al, 2007;Rostas and Wolfling, 2009;Darrouzet et al, 2010) or sexual mates (Syvertsen et al, 1995;Sullivan, 2002;Steiner et al, 2005;Steiner et al, 2006;Sugeno et al, 2006;Geiselhardt et al, 2009;Ferveur and Cobb, 2010;Ginzel, 2010;Ruther et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The non-polar CHCs have been extensively investigated over the past three decades with respect to their role as semiochemicals (Howard, 1993;Singer, 1998;Howard and Blomquist, 2005). A multitude of studies have shown that CHCs are not only involved in the diverse interactions of social insects (Greene and Gordon, 2003;Endler et al, 2004;van Zweden and d'Ettorre, 2010) but also used by many solitary insects as contact stimuli when searching for oviposition sites (Colazza et al, 2007;Rostas and Wolfling, 2009;Darrouzet et al, 2010) or sexual mates (Syvertsen et al, 1995;Sullivan, 2002;Steiner et al, 2005;Steiner et al, 2006;Sugeno et al, 2006;Geiselhardt et al, 2009;Ferveur and Cobb, 2010;Ginzel, 2010;Ruther et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In N. vitripennis, male attraction to females is at least partly related to female-specific cuticular hydrocarbons (Steiner et al 2006). Sex-specific cuticular hydrocarbons also appear to be an important source of mate recognition cues in other Pteromalinae (e.g., Sullivan 2002;Steiner et al 2005Steiner et al , 2007Ruther et al 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many studies have been correlational only, showing statistically significant differences in the amounts and/or types of compounds present, without being able to confirm that any one or any group of these compounds do indeed have a signaling role. Other studies have bioassayed synthesized CHCs to probe the roles of specific compounds, with some success (15)(16)(17)(18)(19)(20)(21)(22). However, this approach is limited by the large number of compounds in CHC extracts so that a single study might require syntheses of numerous standards to assess the functional roles of all possible components.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl-branched cuticular hydrocarbons (MBCHs) have been identified or implicated as contact pheromones in a number of insect species (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), but most studies involving MBCHs have ignored the issue of stereochemistry and used only racemic MBCHs in bioassays to assess function. The linked questions as to whether insects biosynthesize MBCHs enantioselectively and whether insects can discriminate between the stereoisomeric Significance Methyl-branched hydrocarbons (MBCHs) are widely used for inter-and intraspecific communication by insects.…”
mentioning
confidence: 99%